Corporate social responsibility in China : cultural and ownership influences on perceptions and practices - ZHANG, DASHI (Communication, culture and change in Asia, 2017)
This book explores how the traditional Chinese culture and business ownership influence corporate social responsibility in China. By comparing state-owned enterprises, private companies and multinational companies, it shows how corporate social responsibility is perceived and practiced at the corporate level in these companies. It also studies how intertwined company practices and the Chinese culture are, and how this relationship affects the business environment in China. Further, it highlights the value of economic factors in corporate social responsibility, and the influence of Chinese philosophy on corporate ethics. It is a valuable tool for researchers and academics wishing to understand the dynamics of corporate social responsibility in China and discover the significant influencing factors in China's business arena.